A Vindication of the Spanish Mother. Maternal Images in the Filmic Make-over of the Nation - Andrés Zamora (Studies in 20th & 21st Century Literature, 2009)
The maternal figure as an explicit or oblique image of the Spanish nation has undergone a good share of indignities throughout the modern cultural history of the country, from the nineteenth-century Mater Dolorosa to the stepmother of those forced into exile after the civil war, from the terrible matriarchs of Benito Peréz Galdós, Federico Garcia Lorca and Camilo José Cela to the patriarchal mothers of Spanish oppositional cinema in the final phase of the dictatorship and first years of the democratic transition. This latter avatar of the Spanish mother, so well reconstructed by Marsha Kinder, had the bewildering destiny of being both the displaced incarnation of authoritarian power and the object of the rebellion and the violent ire of her offspring. After the demise of the Franco regime, one of the most urgent tasks of the new democratic period was to produce a redefinition of the Spanish national identity, sequestered and monopolized for so many years by the ideological patchwork of the dictatorship. Towards that end, contemporary Spanish cinema has undertaken an extraordinary revision and vindication of the mother against the dire history of her evil or martyred antecedents, as a fundamental, though subtle, gesture in the attempt to rebuild, suture, and make over the nation.
Keywords: Spain; mother; motherhood; maternal images; nation; Mater Dolorosa; Galdós; Garcia Lorca; José Cela; oppositional cinema; Marsha Kinder; national identity